EFFORTS OF SUBJECT TEACHER CONSULTATIONS (MGMP) IN INCREASING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION LEARNING - Suhiroh, Iroh; Tharihoran, Naf’an; Hidayatullah, Hidayatullah (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The purpose of the research that the author did was to find out and explore the efforts of MGMP to improve the quality and quality of Islamic Religious Education Learning. This research is descriptive qualitative research with the type of field research. Methods of collecting data were observation, open interviews and study documentation. Data analysis used descriptive analysis. The results of the study found facts that efforts MGMP to improve the quality of Islamic Religious Education Learning at SMP-IT Ibadurrahman were carried out by increasing teacher professionalism, improving classroom management and management, and utilizing the habituation programmed in schools. These three efforts are integrated in intracurricular activities, extracurricular activities and habituation activities and school culture. The supporting factors in this case are the existence of evaluation evaluations in one week, the existence of various extra activities and habituation, the existence of cognate lessons that support PAI learning, adequate facilities and support from school stakeholders and foundations. The inhibiting factors of these activities include the ability of teachers to understand and apply approaches, strategies, models and learning methods, teachers tend to do conventional learning with lectures, focusing on cognitive abilities alone.